Design of Rule Based Algorithm Based on IoT (Internet of Things) and Water Level Sensor to Monitor the Tide of Bengawan Solo - zu fahim, wahyu; Handoyo, Eko; Shodiq, Muhammad (Indonesian Journal of Engineering, Science and Technology, 2024)
Laren Village in Laren District, Lamongan Regency, is traversed by the Bengawan Solo River, which is crucial for agriculture, fisheries, industry, and domestic needs. However, excessive use poses risks of pollution and flooding. Floods can cause material losses, infrastructure damage, environmental contamination, disease outbreaks, traffic disruption, and water scarcity. Effective mitigation measures are vital to reduce these risks. Internet of Things (IoT)-based technology offers an effective solution for flood risk mitigation. IoT enables real-time monitoring and decision-making using rule-based algorithms that analyze data patterns, set conditions, and automatically respond to potential threats. On August 6, 2024, observation data showed Bengawan Solo's water level ranged between 119 cm and 170 cm, mostly categorized as "Safe." However, the last two measurements, at 117 cm and 119 cm, shifted the status to "Caution," signaling a need for vigilance. The average water level of 151.7 cm indicated an overall "Safe" condition, yet the sudden drop underscores the importance of continuous monitoring. IoT systems with rule-based algorithms can detect real-time changes, enabling swift risk mitigation. This technology enhances safety, supports environmental sustainability, and preserves the Bengawan Solo River's ecosystem.   Keywords¾ Flood, IoT, Rule Based Algorithm, Telegram, Ultrasonic Sensor,